Risk of HIV and Hepatitis B and C Over Time Among Men Who Inject Image and Performance Enhancing Drugs in England and Wales: Results From Cross-Sectional Prevalence Surveys, 1992–2013. (1st March 2016) - Hope, Vivian D.; Harris, Ross; McVeigh, Jim; Cullen, Katelyn J.; Smith, Josie; Parry, John V.; DeAngelis, Daniela; Ncube, Fortune
Abstract : Background: Infection risks among people who inject drugs (PWID) are widely recognized, but few studies have focused on image and performance enhancing drugs (IPEDs). Globally, concern about IPED injection has increased and, in the United Kingdom, IPED injectors have become the largest group using Needle and Syringe Programmes. Blood-borne virus prevalence trends among IPED injectors are explored. Method: Data from 2 surveys of IPED injectors (2010–2011; 2012–2013) and the national bio-behavioral surveillance system for PWID (1992–1997; 1998–2003; 2004–2009) were merged. Psychoactive drug injectors and women were excluded. Logistic regression analyses explored temporal changes. Results: Between 1992 and 2009, median age increased from 25 to 29 years (N = 1296), years injecting from 2 to 4. There were 53 men who had sex with men (MSM). Overall, 0.93% had HIV, 4.4% ever had hepatitis B (HBV), and 3.9% hepatitis C (HCV, from 1998, N = 1083). In multivariable analyses, HIV increased in 2004–2009 [adjusted odds ratio (AOR) = 10 (95% confidence interval (CI): 0.94 to 106) vs. 1992–2003], and remained elevated (AOR = 4.12, 95% CI: 0.31 to 54, 2012–2013); HBV also increased in 2004–2009 (AOR = 3.98, 95% CI: 1.59 to 9.97). HCV prevalence increase was only borderline significant (AOR = 2.47, 95% CI: 0.90 to 6.77, 2010–2011). HIV and HBV were associated with MSM and HCV with sharing needles/syringes. Uptake of diagnostic testing for HIV and HCV, and HBV vaccination increased (to 43%, 32% and 44% respectively). Condom use was consistently poor; needle/syringe sharing occurred. Conclusion: Blood-borne virus prevalences among IPED injectors have increased and for HIV, is now similar to that among psychoactive drug injectors. Targeted interventions to reduce risks are indicated. Abstract : Supplemental Digital Content is Available in the Text.